A Study on Water Quality of Futala Lake, Nagpur City, Maharashtra, India - Salahuddin (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
Water is very important to sustain life. The rapid growth of population, combined with technological and industrial expansion, has resulted in significant environmental degradation. Freshwater lakes, crucial for the country’s economy, play diverse roles in supporting industrial, agricultural, and ecological processes. Despite the significance of lakes, rising human activities globally, including in India, are degrading the quality of lake water, posing threats to biodiversity and also to human health. This chapter deals with the study of Futala Lake water. The water of Futala Lake is debased due to substantial release of contaminated materials without acceptable treatment to expunge pernicious compounds. Water quality checking and review of the Futala Lake was implemented for numerous physico-chemical parameters in the winter season during 2015-2016. These components are: (i) pH, (ii) Electric Conductivity, (iii) Dissolved Oxygen, (iv) Biochemical Oxygen Demand, (v) Chemical Oxygen Demand, (vi) Total Phosphorous, (vii) Suspended Solid (viii) Total Nitrogen and (ix) Total Coli forms respectively. Statistical analyses, like Pearson Correlation matrix and Cluster analysis, were carried out on the dataset to determine the relationship among the studied parameters. After experimenting with the data, it shows that the maximum parameters are not in the range that is suitable for drinking purposes. So, it is clear that the water of the lake is not suitable for drinking and domestic purposes. Also, it is not suitable for waterborne species. It needs suitable measurement so that the lake water will be suitable for use.